Integration of manufacturing constraints into multi-material topology optimization - Kopatsch, Jan; Polzer, Markus; Bartz, Marcel; Wartzack, Sandro (DS 133: Proceedings of the 35th Symposium Design for X (DFX2024), 2024)
Multi-material topology optimization (MMTO) offers lightweight design potential compared to single-material topology optimization (SMTO). For integrating restrictions of manufacturing processes into a MMTO ordered SIMP model, a mapping scheme is used to assign them only to the relevant material sections. By filtering and projection of the design variables, manufacturing constraints are implemented without considerable increase in optimization effort. Optimization results are compared by objective function values, convergence and effects of manufacturing constraints. The improved manufacturability of the optimization results can be achieved with only slight reduction in the objective function value, which is due to the restriction of the design space introduced by manufacturing constraints.<br
Keywords: Topology optimization; Multi-material; Ordered SIMP; Manufacturability; Heaviside projection method